PATRON KLIEN ANTARA TAUKE DAN PETANI KARET DI KAMPUNG SUNGAI SELODANG KECAMATAN SUNGAI MANDAU KABUPATEN SIAK - Fadli Miftahul Rizki; Ashaluddin Jalil (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research was conducted in Sungai Selodang Village, Sungai Mandau District, Siak Regency. The problem under study is about ho the form and the factors that cause the Patron-client relationship between the Tauke and Rubber Farmers. In selecting research subject, it is done by selecting based on certain criteria . For the data collection process, the researchcer used interview guildelines and conducted indepth intervies with all research subject ith the aim of obtaining valid data. The result in this study explain that the is a Patron-Client relationship between Tauke and Rubber Farmers. Relationships that have lasted long tim lead to a sense of mutual need. The Relationship between the Tauke and Rubber Farmers is very close because it it tied to several factors such as trush and interrelationship. In addition, the Patron-Client relationship that is formed also last forever due to several economic and social factors. Economic factors in questing such as : Buying and selling relationships, how the Tauke provides price information, payment mechanism, discounting and conflict relationships: and social factors such as: trust relationship in debts, kinship relationships, scial visits and bonuses.. Keyword: Patron-Client, Tauke, Rubber Farmers and Socioeconomic